Digital Literacy and Intrinsic Motivation in Chemistry Learning: A Case Study of High-Achieving Students - Utari Aulia Tianda Saputri; Anggi Desviana Siregar; Tri Saslina Saslina (Department of Chemistry Education, Faculty of Science and Technology, Universitas Islam Negeri Walisongo Semarang, 2025)
This study examines the impact of digital literacy and intrinsic motivation on students' academic success, particularly in chemistry at SMA Negeri 1 Kerinci. Employing a descriptive qualitative approach with a case study design, the research focused on 10 high-achieving students from the National Science Competition (KSN). Data were gathered through observations and in-depth interviews, then analyzed using Miles and Huberman's qualitative analysis method, which involves data reduction, data display, and conclusion drawing. The findings reveal that students with strong digital literacy skills are adept at locating, utilizing, selecting, evaluating, and applying digital information to enhance their learning. These students actively seek information from reliable sources, verify its accuracy, and produce original work. High intrinsic motivation is reflected in their dedicated study habits, persistence, and thorough exam preparation. To maintain motivation, students employ strategies such as effective time management and collaboration with peers. The synergy between strong digital literacy and high intrinsic motivation significantly boosts academic achievement. Thus, fostering both digital literacy and intrinsic motivation is essential in education, especially in science.